Residual Content of Synthetic Pyrethroid Transfluthrin on Bed Sheets, Pillowcases, Bedroom Floors, and Development of Analytical Methods Using GC-MS - Kamka, Vienna D.; Budiman, Senadi; Murniati, Anceu (Department of Chemistry, Faculty of Sciences and Informatics, University of Jenderal Achmad Yani, 2023)
Dengue Hemorrhagic Fever (DHF) is an infectious disease with high morbidity and mortality rates worldwide. Two-fifths of the population lives in areas prone to contracting the dengue virus in tropical and subtropical countries. In Indonesia, dengue disease is an endemic problem that spreads in 33 provinces. One way to prevent the transmission of DHF disease is to kill mosquitoes using mosquito repellent spray, electric or mosquito coils. Regular use of household aerosols for mosquito control is widespread, especially during outbreaks of dengue fever, chikungunya, and Zika. In this study, it will be proven whether, in the use of mosquito repellent made from active transfluthrin, the remaining residue attached to indoor items is still within safe limits if exposed to the skin or inhaled by humans. The purpose of this study was to determine the content of transfluthrin mosquito repellent pesticide residues on the surface of objects in the room still below the maximum limit required using the Gas Chromatography-Mass Spectrometry (GC-MS) tool as well as the development of measurement analysis methods for Lienarity, Recovery, Precision/Specivity, Quantitative Limit, and Detection Limit. The study's results on measuring Transfluthrin residues using GCMS with a data collection height of 100-200 cm obtained a concentration range of 22-149 mg/kg. Validation test of the analysis method obtained LOD: 0.005 (µg/ml), LOQ: 0.016 (µg/ml), RSD system conformance test: 0.118%, Linear Regression Linearity (r2): 0.99946, %Recovery: 102.00%, Placebo specificity: does not show a peak at Transfluthrin retention time.